Repeat genetic testing with targeted capture sequencing in primary arrhythmia syndrome and cardiomyopathy. (December 2017) - Robyns, Tomas; Kuiperi, Cuno; Breckpot, Jeroen; Devriendt, Koenraad; Souche, Erika; Van Cleemput, Johan; Willems, Rik; Nuyens, Dieter; Matthijs, Gert; Corveleyn, Anniek
Abstract In inherited primary arrhythmia syndromes (PAS) and cardiomyopathies (CMP), the yield of genetic testing varies between 20 and 75% in different diseases according to studies performed in the pre next-generation sequencing (NGS) era. It is unknown whether retesting historical negative samples with NGS techniques is worthwhile. Therefore, we assessed the value of NGS-based panel testing in previously genotype negative–phenotype positive probands. We selected 107 patients (47 PAS and 60 CMP) with a clear phenotype who remained genotype negative after genetic analysis of the main genes implicated in their specific phenotype. Targeted sequencing of the coding regions of 71 PAS- and CMP-related genes was performed. Variant interpretation and classification was done according to a cardiology-specific scoring algorithm ('Amsterdam criteria') and the ACMG-AMP criteria. Co-segregation analysis was performed when DNA and clinical data of family members were available. Finally, a genetic diagnosis could be established in 21 patients (20%), 5 PAS (11%) and 16 CMP (27%) patients, respectively. The increased detection rate was due to sequencing of novel genes in 52% of the cases and due to technical failures with the historical analysis in 48%. A total of 118 individuals were informed about their carrier state and either reassured or scheduled for proper follow-up. To conclude, genetic retesting in clinically overt PAS and CMP cases, who were genotype negative with older techniques, resulted in an additional genetic diagnosis in up to 20% of the cases. This clearly supports a policy for genetic retesting with NGS-based panels.